"Tuer le taudis qui nous tuera": crise du logement et discours sur la famille montréalaise d'après-guerre (1945-1960) - Bourbeau, Amélie (Université de Montréal, 2002)
Keywords: Logement; Pauvreté

Ma passion pour Montréal - Bourque, Pierre (Méridien, 2002)
Keywords: Expositions; Jardin botanique

Un enjeu politique: la pasteurisation - Colas, Valéry (Cap-aux-Diamants, 2002)
Keywords: Alimentation; Maires; Martin, Médéric

La revanche du territoire: l'évolution des politiques publiques québécoises en appui aux TIC depuis 1991 - Côté, Guillaume (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2002)

Jacques Parizeau. Tome II - Le Baron - 1970-1985 - Duchesne, Pierre (Biographie, 2002)

L'intervention municipale dans le développement résidentiel, l'opération Habiter Montréal 1990-2001 - Gomez, Élodie (Université de Montréal, 2002)
Keywords: Logement; Évaluation foncière

Anniversaires et manifestations des camarades. La culture internationale et l’identitaire communistes au Canada pendant l’entre-deux-guerres - Lévesque, Andrée (Labour / Le travail, 2002)
Keywords: Communistes

Battles on the Homes Front: Montreal's Response to Federal Housing Initiatives, 1941-1947 - Lyons, Christopher M. (Université Concordia, 2002)
Keywords: Guerre; Logement

From Bourassa to Bourassa: Wilderness to Restoration - MacDonald, L. Ian (McGill-Queen's University Press, 2002)
"From Bourassa to Bourassa is a narrative history of the Quebec Liberal Party during its wilderness years after the 1976 election of the Parti Quebecois and its subsequent restoration in 1985." "First published to critical acclaim in 1984, From Bourassa to Bourassa, 2nd edition, updates the story with Bourassa's landslide election victory in 1985 and his subsequent role in the Meech Lake Accord and the Canada-U.S. Free Trade Agreement, the two issues that largely defined the decade of the 1980s for Quebec and for Canada."--BOOK JACKET.
Keywords: Bourassa, Robert; Partis politiques

La construction politique d'un quartier: St-Michel et la controverse sur la carrière Miron - Martin, Alain (Institut national de la recherche scientifique et Université du Québec à Montréal, 2002)
Keywords: Carrière; Carrière Miron; Quartiers; Saint-Michel

Le Devoir et le groupe des conservateurs-nationalistes après les élections fédérales du 21 septembre 1911 - Moreau, Aurélie (Université d'Angers, 2002)
Keywords: Devoir (Le); Nationalisme; Élections

Le rôle des références patrimoniales dans la construction des politiques urbaines à Bordeaux et Montréal - Paulhiac, Florence (Institut national de la recherche scientifique et Université Michel de Montaigne-Bordeaux 3, 2002)
Keywords: Bordeaux; Conservation; Patrimoine; Quartiers; Vieux-Montréal

Wilfrid Laurier: A Pledge for Canada - Stewart, Roderick (XYZ, 2002)

The Defeat of George-Etienne Cartier in Montreal-East in 1872 - Young, Brian J. (The Contested Past: Reading Canada's History - Selections from the Canadian Historical Review, 2002)
Keywords: Cartier, George-Étienne